ClfA221–550, a fibrinogen-binding segment of Staphylococcus aureus clumping factor A, disrupts fibrinogen function - Liu, Chao-Zong; Shih, Mei-Hsu; Tsai, Pei-Jane (Thrombosis and Haemostasis, 2005)
Clumping factor A (ClfA) is a surface of protein Staphylococcusaureus bacteria known for its ability to bind the C-terminus of plasma fibrinogen γ chain, which participates in mediating fibrinogen- platelet interaction and fibrin cross-linking, resulting in thrombus formation. With an aim to develop agents that block fibrinogen γ chain C-terminus,the fibrinogen-binding segment of ClfA locating at residues 221–550 was produced by recombinant technology and tested for its ability to inhibit platelet functions and fibrin clot formation. Recombinant ClfA221–550 bound fibrinogen and blocked fibrinogen-platelet interaction, resulting in the inhibition of both ADP- and collagen-induced platelet aggregations. ClfA221–550 also affected fibrin clot formation, in which factor XIIIa-mediated cross-linking of fibrinogen γ chains was abrogated by ClfA221–550 leaving the release of fibrinopeptides A and B from fibrinogen by thrombin unaltered, indicating that ClfA221–550 interfered with fibrin clot formation without affecting thrombin’s catalytic activity. Plateletmediated clot retraction depends on both platelet-fibrinogen interaction and fibrin clot formation, which makes platelet thrombus less susceptible to fibrinolysis. At the concentration that reduced platelet aggregation by 40%, ClfA221–550 prevented platelet- mediated clot retraction, whereas the glycoprotein IIb/IIIa antagonist tirofiban needed a higher concentration in inhibiting clot retraction than inhibiting platelet aggregation. By virtue of the multiple effects of ClfA221–550 on platelet aggregation, fibrin clot formation and platelet-mediated clot retraction,the binding of ClfA221–550 to fibrinogen merits further investigation for its potential as a new antithrombotic agent.
Keywords: Fibrinogen; fibrinogen-binding protein; clumping factor A; antithrombosis